Penerapan Problem Based Learning untuk Meningkatkan Hasil Belajar dan Partisipasi Peserta Didik - Elya; Ratnaningsih, Nani (PTK: Jurnal Tindakan Kelas, 2025)
This study is based on findings regarding the low learning outcomes of students, as observed from the initial test results and classroom observations. This study aims to improve the learning outcomes and participation of fourth-grade students at SD Islamic Leader School Tasikmalaya through the implementation of the Problem-Based Learning (PBL) model in the topic of multiplication and division. This study employs a classroom action research method consisting of two cycles, with 22 students from SD Islamic Leader School Tasikmalaya as participants during the first semester of the 2024/2025 academic year. Data collection techniques include observation and learning outcome tests. In the pre-cycle phase, student participation was only 29%, and the percentage of students meeting the Learning Objective Achievement Criteria (KKTP) was 31.82%. After implementing PBL, student participation increased to   60% in cycle I and reached 82% in cycle II, while the percentage of students meeting the KKTP rose to 54.55% in cycle I and 86.36% in cycle II. The implementation of the PBL model has proven effective in improving students' learning outcomes and participation in the topic of multiplication and division.